PELATIHAN PERAWATAN MANDIRI DAN PENCEGAHAN PENYAKIT DEGENERATIF PADA LANSIA DI DESA TARAWEANG - Hasifah, Hasifah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Degenerative diseases are diseases that arise as a result of the aging process, such as diabetes, hypertension, stroke, heart disease and dementia. The aim of this research is to train self-care and prevent degenerative diseases in the elderly in Taraweang village. Method: This research is quantitative research using prepost and post tests. The pre-test and post-test results showed an increase in participants' knowledge of 30% and an increase in skills of 25%. The level of participant satisfaction with training activities reached 85%. Conclusions and suggestions: This community service program has succeeded in increasing the knowledge and skills of elderly people in Taweang Village regarding self-care and preventing degenerative diseases, such as hypertension, diabetes and heart disease. Elderly people show high enthusiasm in participating in training and applying the material provided in their daily lives, such as monitoring blood pressure and blood sugar, improving diet, and increasing physical activity. This program has a positive impact on reducing the number of visits to health centers due to complications from degenerative diseases as well as increasing